Enhancing Local Government Financial Statement Quality: The Role of Apparatus Quality, Technology Utilization, Accounting Policies, and Internal Control - Winda Febri Lestari W.R; Robinson; Rini Indriani (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study aims to examine the influence of the quality of financial management officials and the use of technology on the quality of financial reports, with the application of accounting policies as a mediator and internal control as a moderator. Respondents in this study were financial management officials at 40 Regional Work Units (SKPD) in Central Bengkulu Regency, consisting of 29 Regional Government Organizations and 11 Districts, with a saturated sampling technique. The data analysis tool used in this study was SEM-PLS. The test results show that the quality of financial management officials significantly influences the application of accounting policies, while the use of technology does not. The application of accounting policies significantly influences the quality of financial reports and mediates the effect of the quality of financial management officials on the quality of financial reports, but does not mediate the effect of technology use. Internal control was not proven to moderate the relationship between accounting policies and the quality of financial reports. This study provides one model option for improving the quality of local government financial reports through strengthening the application of accounting policies.